Prenatal ultrasonographic features and follow-up outcomes of 19 cases of congenital intrahepatic portosystemic venous shunts diagnosed during the foetal period - Linlin Zhu; Haifang Wu; Xiang Cong; Shizhen Li; Qi Li; Xiangyi Dong; Guowei Tao (Insights into Imaging, 2022)
Abstract Background To investigate the prenatal ultrasonographic features and case characteristics of the congenital intrahepatic portosystemic venous shunt (IHPSS) diagnosed during the foetal period and analyse its prognosis. Methods We conducted a retrospective cohort study of patients diagnosed with IHPSS between 2016 and 2021. IHPSS was defined as an abnormal connection between the foetal intrahepatic portal and the hepatic veins. Results In this study, 19 foetuses were identified, including 12 cases of single shunt and 7 cases of multiple shunts, with a gestational age of 33.8 ± 4.5 (range 25–40) weeks at diagnosis. In the single-shunt group, the origin position of the shunts was all from the left branch of the portal vein (LPV), whereas in the multiple-shunt group, the origin position of the shunts was from the LPV in six cases. Common concomitant intrauterine abnormalities of IHPSS include foetal growth restriction (47.4%) and foetal cardiac enlargement (21.1%). The postnatal manifestations of IHPSS include biochemical abnormalities (increased gamma-glutamyl transferase and bilirubin levels), neonatal hypoglycaemia, neonatal hyperammonaemia, pulmonary hypertension, multiple intrahepatic hyperechoic nodules, and cutaneous haemangiomas. Spontaneous closure of shunts occurred in ten cases, and the mean time to shunt closure was 8.1 months (1–28 months). Conclusions Most IHPSS found during the foetal period is located in the left branch of the portal vein, and the gestational age at diagnosis is usually in the late second or third trimester. Spontaneous closure of shunts can occur in most live births, and the prognosis is good.